Bias in published cost effectiveness studies: systematic review. Issue 7543 (22nd February 2006) - Bell, Chaim M; Urbach, David R; Ray, Joel G; Bayoumi, Ahmed; Rosen, Allison B; Greenberg, Dan; Neumann, Peter J
Abstract: Objective To investigate if published studies tend to report favourable cost effectiveness ratios (below $20 000, $50 000, and $100 000 per quality adjusted life year (QALY) gained) and evaluate study characteristics associated with this phenomenon. Design Systematic review. Studies reviewed 494 English language studies measuring health effects in QALYs published up to December 2001 identified using Medline, HealthSTAR, CancerLit, Current Content, and EconLit databases. Main outcome measures Incremental cost effectiveness ratios measured in dollars set to the year of publication. Results Approximately half the reported incremental cost effectiveness ratios (712 of 1433) were below $20 000/QALY. Studies funded by industry were more likely to report cost effectiveness ratios below $20 000/QALY (adjusted odds ratio 2.1, 95% confidence interval 1.3 to 3.3), $50 000/QALY (3.2, 1.8 to 5.7), and $100 000/QALY (3.3, 1.6 to 6.8). Studies of higher methodological quality (adjusted odds ratio 0.58, 0.37 to 0.91) and those conducted in Europe (0.59, 0.33 to 1.1) and the United States (0.44, 0.26 to 0.76) rather than elsewhere were less likely to report ratios below $20 000/QALY. Conclusion Most published analyses report favourable incremental cost effectiveness ratios. Studies funded by industry were more likely to report ratios below the three thresholds. Studies of higher methodological quality and those conducted in Europe and the US rather than elsewhere were less likely to report ratios below $20 000/QALY.